2020
DOI: 10.1108/ijmce-10-2019-0096
|View full text |Cite
|
Sign up to set email alerts
|

“First meetings”: constructive first encounters between pre-service teachers and their mentors

Abstract: PurposeThe purpose of this paper is to report the findings from an action research project in which the researchers sought to develop a set of questions for use by mentors (experienced teachers) and mentees (pre-service teachers) on a course of initial teacher education (ITE) when they first met – the “initial encounter”.Design/methodology/approachThe researchers used an action research approach in order to address the lower retention rate of pre-service teachers from different backgrounds, such as Black and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This is seen both in terms of teacher retention and recruitment beyond the Initial Teacher Training (ITT), with 20% of teachers in the United Kingdom leaving the profession within 2 years and 33% within 5 years; based on data as of 2017 (DfE, 2019d). High attrition rates of some ITT groups, such as BAME (Black, Asian, and minority ethnic), prompted a study of ITT mentoring by Connolly et al (2021), which highlighted mentoring inexperience. Sosssick et al's (2019) case study of mentoring and coaching showed potential resilience building through a "third space"; shifting the CPD/PD mentoring/coaching model away from outcomes-based judgement.…”
Section: Why Have Schoolteacher Mentors?mentioning
confidence: 99%
“…This is seen both in terms of teacher retention and recruitment beyond the Initial Teacher Training (ITT), with 20% of teachers in the United Kingdom leaving the profession within 2 years and 33% within 5 years; based on data as of 2017 (DfE, 2019d). High attrition rates of some ITT groups, such as BAME (Black, Asian, and minority ethnic), prompted a study of ITT mentoring by Connolly et al (2021), which highlighted mentoring inexperience. Sosssick et al's (2019) case study of mentoring and coaching showed potential resilience building through a "third space"; shifting the CPD/PD mentoring/coaching model away from outcomes-based judgement.…”
Section: Why Have Schoolteacher Mentors?mentioning
confidence: 99%